Agitating for Change: Theatre and a Feminist 'Network of Resistance'. Issue 1 (11th February 2016) - ASTON, ELAINE
Abstract : Focusing on the UK, where feminism is gaining momentum through multiple sites of activist dissent from a neoliberal hegemony, my primary concern in this article is to understand how, given this renewal of feminist energies, theatre might be able to play its part in agitating for change. Inspired by Chantal Mouffe's compelling description of a 'network of resistance', as a possible way forward I conceive of theatre politically as a series of heterogeneously formed sites of oppositional and affirmative activity, each linked into articulating dissent from neoliberalism and the desire for socially progressive change. This provides the critical framework for my engagement with three radically diverse performances ranging from new playwriting (Lucy Kirkwood's NSFW ), through the flash mob (Eve Ensler's One Billion Rising campaign), to the West End musical Made in Dagenham .